2023
DOI: 10.1111/eip.13434
|View full text |Cite
|
Sign up to set email alerts
|

Baseline antipsychotic prescription and short‐term outcome indicators in individuals at clinical high‐risk for psychosis: Findings from the Parma At‐Risk Mental States (PARMS) program

Abstract: AimThe prognostic prediction of outcomes in individuals at clinical high‐risk for psychosis (CHR‐P) is still a significant clinical challenge. Among multiple baseline variables of risk calculator models, the role of ongoing pharmacological medications has been partially neglected, despite meta‐analytical evidence of higher risk of psychosis transition associated with baseline prescription exposure to antipsychotics (AP) in CHR‐P individuals. The main aim of the current study was to test the hypothesis that ong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
(61 reference statements)
1
4
0
Order By: Relevance
“…The findings in this systematic review and meta-analysis confirmed that among individuals at CHR-P who were exposed to antipsychotics at baseline (ie, a specific CHR-P subgroup with even higher documented higher risk of transition to psychosis [1][2][3][4] ), those who converted to psychosis were prescribed higher antipsychotic doses compared to those who did not convert. The results were congruent between the commoneffects model and the random-effects models, with an effect size approaching a moderate level.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…The findings in this systematic review and meta-analysis confirmed that among individuals at CHR-P who were exposed to antipsychotics at baseline (ie, a specific CHR-P subgroup with even higher documented higher risk of transition to psychosis [1][2][3][4] ), those who converted to psychosis were prescribed higher antipsychotic doses compared to those who did not convert. The results were congruent between the commoneffects model and the random-effects models, with an effect size approaching a moderate level.…”
Section: Discussionsupporting
confidence: 69%
“…Our search yielded 2008 articles, 425 of which were assessed by full text and 8 of which met the inclusion criteria (eFigure 1 in Supplement 1). The Table synthetizes the main characteristics of the included studies, 4,[8][9][10][11][12][13][14] whereas their general characteristics are reported in the eResults in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations